A fiery friendship - Fiedler, Lisa (Fiedler, Lisa. Gabriel Gale's Ages of Oz., 2017)
When her mother is imprisoned for practicing forbidden Magic, thirteen-year-old Glinda must save the future of Oz from the four Wicked Witches.